Adverse pregnancy and neonatal outcomes associated with Neisseria gonorrhoeae, Mycoplasma genitalium, M. hominis, Ureaplasma urealyticum and U. parvum: a systematic review and meta-analysis protocol. Issue 11 (28th November 2018) - Vallely, Lisa M; Egli-Gany, Dianne; Pomat, William; Homer, Caroline SE; Guy, Rebecca; Wand, Handan; Silver, Bronwyn; Rumbold, Alice R; Kaldor, John M; Low, Nicola; Vallely, Andrew J
Abstract : Introduction: Several bacterial sexually transmitted and genital mycoplasma infections during pregnancy have been associated with poor pregnancy and perinatal outcomes. Comprehensive and systematic information about associations between sexually transmitted infections (STI) and genital infections in pregnancy and adverse perinatal outcomes is needed to improve understanding about the evidence for causal associations between these infections and adverse pregnancy and neonatal outcomes. Our primary objective is to systematically review the literature about associations between: (1) Neisseria gonorrhoeae in pregnancy and preterm birth; (2) Mycoplasma genitalium in pregnancy and preterm birth; (3) M. hominis, Ureaplasma urealyticum and/or U. parvum in pregnancy and preterm birth. Methods and analysis: We will undertake a systematic search of Medline, Excerpta Medica database and the Cochrane Library and Cumulative Index to Nursing and Allied Health Literature. Following an initial screening of titles by one reviewer, abstracts will be independently assessed by two reviewers before screening of full-text articles. To exclude a manuscript, both reviewers need to agree on the decision. Any discrepancies will be resolved by discussion, or the adjudication of a third reviewer. Studies will be included if they report testing for one or more of N. gonorrhoeae, M. genitalium, M. hominis, U. urealyticum and/or U. parvum during pregnancy and report pregnancy and/or birth outcomes. In this review, the primary outcome is preterm birth. Secondary outcomes are premature rupture of membranes, low birth weight, spontaneous abortion, stillbirth, neonatal mortality and ophthalmia neonatorum. We will use standard definitions, or definitions reported by study authors. We will examine associations between exposure and outcome in forest plots, using the I 2 statistic to examine between study heterogeneity. Where appropriate, we will use meta-analysis to combine results of individual studies. Ethics and dissemination: This systematic review of published literature does not require ethical committee approval. Results of this review will be published in a peer reviewed, open access journal. PROSPERO registration number: CRD42016050962.